O constitucionalismo sob a ótica de Evguiéni B. Pachukanis - Dias, Bruno Carniato (2024)
The present work aims to present the constitucionalism and expose it under the optics of marxist Law theory proposed by Eviguéni B. Pachukanis. Its academic relevance is unveiled by the reading of a Law theory branch under the perspective of the marxist philosophy, contributing to a literature review of the theme. To this, the constitucionalism will be exposed as a movement of limitation of the State political power developed throug the time. The expostition will be consisted by an historic philosophical analysis of the movement, bringing Hans Kelsen to discussion as a theorical expoent of theory of Law. The choose of bringing Kelsen to discussion was given by two factors: the author debated directly with Pachukanis; Kelsen´s theory is fundamental to the understanding of conteporary Law and the constitucionalismo. To this two of his works were choosen: Pure Theory of Law and Constitutional Jurisdiction. The second chapter will explore and expose the marxista theory of Law developed by Pachukanis by exploring the commodity form in Marx to expose the Law ideological nature. On the final chapter both theories will be tied, bringing the Pachukanis critics to Kelsen and the constitucionalism. This chapter will also show the authors view about the construction of a socialist Law at the same time as its theory points forward to the end of the legal-form as a consequence of the end of the end of the commodity form, or, by other means, the creation of Law that will self dilute.